Usability Analysis of Digital Learning Media Based on Google Sites Using the SUS Scale - Rostika, Neneng; Abidin, Yunus; Kurniawan, Dede Trie (Journal of Basic Education Research, 2025)
Purpose of the study: This study aims to evaluate the usability of digital learning media developed using Google Sites through a systematic and standardized measurement approach. The main focus is to identify whether the media is easy to use, engaging, and acceptable from the users’ perspective. Methodology: This study employed the System Usability Scale (SUS) method, combined with a literature review of related studies. The SUS questionnaire was used as the main tool for data collection, while scoring and analysis were performed with standardized calculation procedures to evaluate usability outcomes. Main Findings: The results showed that the digital learning media developed with Google Sites achieved an average SUS score of 79. This score falls into the “Good” category, equivalent to a grade scale of C, and is classified as “acceptable.” Users demonstrated positive perceptions regarding its usability, indicating effectiveness while also highlighting the need for further development. Novelty/Originality of this study: This study provides new insights into usability evaluation of Google Sites as a digital learning medium using the SUS method. It contributes by highlighting practical user perceptions and offering evidence-based recommendations for further improvement, thereby expanding knowledge about effective integration of accessible online platforms in education.